THE HISTORY OF FOLKLORE OF THE ZARAFSHAN OASIS IN THE DEVELOPMENT OF YOUTH IN CENTRAL ASIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article explores the folk oral creativity of the Uzbek people, particularly through the lens of the Zarafshan Oasis. It underscores the historical importance of folklore and oral traditions passed down from our ancestors, highlighting their role in educating the younger generation to become spiritually mature, well-educated, and compassionate individuals. The study also points out that the Turkic peoples have long been an integral part of the region’s shared cultural and historical heritage. In recent years, Uzbekistan has experienced a renewed interest in thoroughly and objectively studying the history of science, education, culture, and long-standing values. There has been a particular focus on understanding and appreciating the rich musical and oral heritage of the past. Folklore, recognized as one of the oldest forms of folk culture, reflects the lifestyle, wisdom, experiences, achievements, and aspirations of the people. Passed down through generations, it has served as a “school of life” playing a crucial role in the moral and spiritual development of youth. Folk oral creativity, embodying the spirit, sincerity, and unique beauty of ancient culture, is considered a priceless spiritual treasure – an endless source that has nourished the hearts, minds, and emotions of people for centuries. The continuous development of folk traditions and their integration into the lives of younger generations is a vital and ongoing process. The achievement of national independence and Uzbekistan’s growing recognition in the international community have allowed the field of folkloristics to advance as a significant historical and cultural phenomenon. The primary objective of this article is to strengthen intercultural relations, promote essential human qualities such as friendship and mutual respect, and contribute to the stability of interethnic relations.
Keywords: Folklore, artistic word, history of literature, Zarafshan Oasis, Youth Education, Art of Turkic peoples, types of folklore genres.